Crossover between the extended and localized regimes in stochastic partially self-avoiding walks in one-dimensional disordered systems - Berbert, Juliana Militão [UNESP]; Martinez, Alexandre Souto (American Physical Society (APS), 2010)
Consider N sites randomly and uniformly distributed in a d -dimensional hypercube. A walker explores this disordered medium going to the nearest site, which has not been visited in the last μ (memory) steps. The walker trajectory is composed of a transient part and a periodic part (cycle). For one-dimensional systems, travelers can or cannot explore all available space, giving rise to a crossover between localized and extended regimes at the critical memory μ1 = log2 N. The deterministic rule can be softened to consider more realistic situations with the inclusion of a stochastic parameter T (temperature). In this case, the walker movement is driven by a probability density function parameterized by T and a cost function. The cost function increases as the distance between two sites and favors hops to closer sites. As the temperature increases, the walker can escape from cycles that are reminiscent of the deterministic nature and extend the exploration. Here, we report an analytical model and numerical studies of the influence of the temperature and the critical memory in the exploration of one-dimensional disordered systems. © 2010 The American Physical Society.